Comparison of Two Different Intervals of Misoprostol Administration in Second Trimester Abortions - Anjali Gupta; Sarika Gautam; Shelly Chanana; Neetu Sangwan; Savita Rani Singhal; Smriti Anand; Sonia Dahiya (Tehran University of Medical Sciences, 2023)
Objective: Comparison of two different intervals of misoprostol administration after mifepristone in second trimester abortions. Materials and methods: This 12-month prospective study was conducted at a tertiary care facility. Only pregnancies with congenital deformity or sterilisation failure were included in the study's recruitment of 100 women who visited the hospital for a second trimester abortion between 12 and 20 weeks; cases with scarred uteri were omitted. In a systematic random selection of 50 women in each group, the administration of 200 mg of mifepristone orally was followed by two distinct intervals of intravaginal misoprostol administration at 24- and 48-hour intervals. After 24 hours, group A women received intravaginal 400 mcg misoprostol three hourly, up to a maximum of five doses, while group B received the same doses after 48 hours. Induction abortion interval noted on various parameters and paired t test and chi square test applied. Results: The mean IAI following misoprostol administration was 8.14 2±.03 hours in group A and 7.71 ±2.56 hours in group B. This difference was statistically insignificant. Average misoprostol doses for group A were 1.68±0.71 and for the group, B were 1.68±0.84; both doses were found to be statistically insignificant when used to induce abortion. All women aborted successfully in each group. There was no significant difference in side effects in both groups. Conclusion: Based on the results it was observed that shorter interval between mifepristone and misoprostol i.e., 24 hours can be chosen to decrease the hospital stay as there was no significant difference was seen after intravaginal misoprostol in terms of  induction abortion interval, number of doses and side effects.